Evaluation of the Levels and Quality of Microbial Contamination in Medical Emergency Departments in Comparison to Other Workplaces - Agata Bielawska-Drózd; Bożena Wlizło-Skowronek; Piotr Cieślik; Izabela Winnicka; Ewa Skopińska-Różewska; Leszek Kubiak; Dorota Żakowska; Aleksandra Brewczyńska; Janusz Kocik (Polish Journal of Microbiology, 2016)
Work in Hospital Emergency Departments (HEDs) exposes both the emergency ward staff and patients to infectious and in other way harmful biological agents. The results of this study shows the presence of pathogenic bacteria isolated by three different methods. It revealed 9.8% of pathogens detected by imprint method, 10.5% of pathogens by swabbing method, 17.6% and 22% in HEDs corridors and rooms, respectively, by air sampling method. In control workplaces (offices) pathogenic bacteria reached the level of 6.5% and 14.7% by imprint method and swabbing, respectively. The relatively low level of contamination by bacteria in HEDs may depend on the effectiveness of Standard Protective Precautions in the studied hospitals.